Назви комп’ютерних вірусів у сучасній українській комп’ютерній субмові - Бондарчук, Л. (Лексикографічний бюлетень, 2011)
The article analyzes the peculiarities of the origin, formation and operation of computer
virus names in the modern Ukrainian language, and classification of computer viruses. An
attempt is made to classify the names of computer viruses on several key indicators: the
place of origin, number of bytes, author, date activated, action, visual effects and more.